Transcriptome profiling of symptomatic vs. asymptomatic grapevine plants reveals candidate genes for plant improvement against trunk diseases - M. Patanita; M. D. Campos; A. Albuquerque; J. A. Ribeiro; D. Pimentel; R. S. Ramiro; T. Monteiro; M. Basaloco; F. Santos; I. Castro; M. R. Félix (BMC Plant Biology)
Abstract Background Grapevine trunk diseases (GTDs) are a disease complex that pose a serious challenge to vineyard productivity worldwide. Their increasing occurrence, coupled with the absence of effective treatments, turns their incidence one of the biggest obstacles to viticulture. A deeper understanding of grapevine defence mechanisms is essential to develop new strategies for a sustainable disease management. Results This study explored the transcriptome profiling of GTDs symptomatic and asymptomatic plants of ‘Trincadeira’ (a slightly susceptible or tolerant cultivar to GTDs) and ‘Alicante Bouschet’ (a highly susceptible susceptible or susceptible cultivar to GTDs), under natural field conditions. RNA-seq yielded 1 598 differentially expressed genes (DEGs) when comparing cultivars, and 64 DEGs associated with symptomatology, regardless of the cultivar. Transport was revealed as the main biological process involved, predominantly activated in ‘Alicante Bouschet’, indicating a possible link between these genes and disease progression. Conversely, the relative tolerance of ‘Trincadeira’ to this disease complex might be supported by the activation of secondary and hormonal metabolism and the differential expression of a set of defence-related genes, which may act as key factors to limit GTDs infection. An important role of the peroxidase gene PER42 in the inhibition of GTDs symptoms was highlighted in this study. Conclusions Our results provide novel insights into grapevine resistance mechanisms to GTDs and highlight candidate genes for improving disease tolerance. To the best of our knowledge, this is the first transcriptomic study of naturally infected grapevines with multiple trunk pathogens under natural field conditions. By modulating the activation or inhibition of key plant response regulators, it may be possible to enhance resistance, offering sustainable and effective strategies for successful management of GTDs. Clinical trial number Not applicable.